Hubungan Tekanan Darah dengan Volume Pendarahan Intraserebral pada Pasien Stroke Hemoragik di Ruang Rawat Inap Saraf Rumkital Dr Ramelan Surabaya - Kenny Yulian; Olivia Mahardani Adam; Lestari Dewi (HANG TUAH MEDICAL JOURNAL, 2019)
ABSTRACT Background.Hemorrhagic stroke is a spontaneous bleeding in the brain that is usually life threatening. The most common risk factor of hemorrhagic stroke is hypertension. Hypertension can cause change in the structure of the artery wall which can cause the blood vessels near the brain to rupture easily. Purpose. To analyze the correlation between blood pressure and intracerebral haemorrhage volume in hemorrhagic stroke patients in Dr.Ramelan Navy Hospital neurologic ward. Method. This research is using a cross sectional study design. This study is done using primary data collection, using the head CT Scan result to measure the patient’s intracerebral hemorrhage volume and patient’s ER admission data for the blood pressure. Results. The study is performed to 26 haemorrhagic stroke patients who fits the inclusion and exclusion criteria. Correlation test shows no correlation between blood pressure and intracerebral haemorrhage volume in haemorrhagic stroke patients in Dr.Ramelan Navy Hospital neurologic ward, with significance (p) value of 0.888 > α (0.05). Conclusion. There is no correlation between blood pressure and intracerebral haemorrhage volume in haemorrhagic stroke patients in Dr.Ramelan Navy Hospital neurologic ward.